La Organización Mundial del Comercio y el medio ambiente: algunos alcances - Zúñiga Schroder, Humberto (2016)
The environment preservation and protection is one of the objectives of the World Trade Organization, as stated in the Marrakech Agreement which set up such organization. Even though the WTO is not an environmental entity, environmental issues take part of its interests.In this article, the author analyzes the main rules and legal instruments generated within the World Trade Organization, including several multilateral agreements that impact and influence in the treatment of environmental issues.